2022
DOI: 10.1002/ps.7107
|View full text |Cite
|
Sign up to set email alerts
|

Repellence or attraction: secondary metabolites in pepper mediate attraction and defense against Spodoptera litura

Abstract: BACKGROUND Resistance to insect pests is an important self‐defense characteristic of pepper plants. However, the resistance of different pepper cultivars to Spodoptera litura larvae, one of the main insect pest species on pepper, is not well understood. RESULTS Among seven pepper cultivars evaluated, cayenne pepper ‘FXBX’ showed the highest repellency to third instar S. litura larvae, Chao tian chili pepper ‘BLTY2’ showed the lowest repellency. Plant volatiles (1‐hexene, hexanal, β‐ionone, (E,E)‐2,6‐nonadienal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…In the literature, it has been stated that secondary metabolites, which are the defense metabolites of plants, cause a decrease in the pupa mass of insects. According to Yuan et al (2022), it was determined that pupal weights of Spodoptera litura (Lepidoptera: Noctuidae) individuals fed with different pepper plants decreased with the amount of flavonoids. Similarly, Harvey et al (2007) reported that the pupal mass of Manduca sexta (Lepidoptera: Sphingidae) was negatively correlated with nicotine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it has been stated that secondary metabolites, which are the defense metabolites of plants, cause a decrease in the pupa mass of insects. According to Yuan et al (2022), it was determined that pupal weights of Spodoptera litura (Lepidoptera: Noctuidae) individuals fed with different pepper plants decreased with the amount of flavonoids. Similarly, Harvey et al (2007) reported that the pupal mass of Manduca sexta (Lepidoptera: Sphingidae) was negatively correlated with nicotine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The EAG test was based on the same method used for the determination of antennally-active volatiles for tea geometrids (Yuan et al 2022). The EAG system (Syntech, Ltd., Hilversum, The Netherlands) consisted of an IDAC-4 interface box, a CS-55 air stimulus controller, and a desktop computer.…”
Section: Eag Experimentsmentioning
confidence: 99%
“…Adults detect volatile organic compounds (VOCs) emitted by plants in a speci c way, discriminating between different resistant plants or cultivars based on the types and proportions of volatile compounds (Ranger et al 2005;Huang et al 2022). Volatiles from non-host plants or resistant cultivars contain repellent components to prevent herbivorous insect infestation (Yuan et al 2022). For example, Rosmarinus o cinalis, a non-host plant with speci cally bioactive compounds in its volatiles that repelling Ectropis obliqua adults (Zhang et al 2015); ocimene, a dominant component of resistant wheat varieties repelled Sitodiplosis mosellana females (Huang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been conducted on S. litura and chili peppers; one study found that feeding S. litura with chili peppers treated with methyl jasmonate significantly decreased its relative growth rate 10 . Another study found that some plant volatiles (1‐hexene, hexanal, β ‐ionone, ( E , E )‐2,6‐nonadienal, and methyl salicylate) affected the host selection of S. litura 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 Another study found that some plant volatiles (1-hexene, hexanal, ⊎-ionone, (E,E)-2,6-nonadienal, and methyl salicylate) affected the host selection of S. litura. 11 Plant defense mechanisms against insect attacks can be categorized into two groups depending on their mode of action: direct defense and indirect defense. 12 Direct defense mechanisms involve the production of chemicals (e.g., gossypol, salicin, dimboa) [13][14][15] by plants that directly harm insect herbivores, whereas indirect defense mechanisms increase the mortality of insect herbivores by recruiting natural enemies.…”
Section: Introductionmentioning
confidence: 99%